Covid-19 and Its Link to Victimization Among College Students - Daigle, Leah E. (American journal of criminal justice, 2021)
In late 2019, the first cases of the disease (Covid-19) caused by the novel coronavirus SARS-CoV2 were discovered. A few months later, a global pandemic was declared that resulted in many lock-down orders across the U.S. These orders and the pandemic itself have sparked research examining the link between Covid-19 and crime. Relevant to the current study, a few studies have found a link between Covid-19 and domestic violence victimization, with many noting significant increases in domestic violence during the pandemic. Some research has also shown that victims are reaching out to domestic violence hotlines at increased rates. Despite these early studies, little is known about how Covid-19 is related to victimization, especially to types other than domestic violence, and how victims may fare during the pandemic. Thus, the current study addresses these gaps by using national level college student data from Fall 2020. Findings show that about 14% of students indicated they had a confirmed test or had symptoms consistent with Covid-19 without a confirmed test. Additionally, having a Covid-19 diagnosis or symptoms were related to all four victimization types and polyvictimization, and being a victim and a polyvictim were related to increased Covid-19-related stress and financial problems. Lastly, victims had increased odds of feeling like psychological or mental health services were somewhat or much more difficult to access during the pandemic relative to non-victims. It may be beneficial for universities to prioritize victims for outreach and consider using resources to modify counseling and other mental health services to better serve their students.